Curative Effect of the Butanol Fraction of Root Bark of Gardenia gummifera L.f against N-nitrosodiethylamine-induced Hepatocellular Carcinoma in Experimental Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Gardenia gummifera Linn. f. belongs to the family Rubiaceae, which is found in rocky hilltops, widely used in traditional medicine. As the plant is rich in active phytoconstituents, there is immense scope for future researches that targeted the studies on experimental animals against various ailments that have been entertained. Curative efficacy of butanol fraction of ethanol extract of root bark of G. gummifera L.f was evaluated on N’Nitrosodiethylamine induced hepatocellular carcinoma in experimental rats. The curative efficacy of two doses of G. gummifera butanol fractions (100 mg/kg bw and 200 mg/kg bw) was evaluated against NDEA induced liver cancer in male Wistar rats. At the end of the experiment, animals were sacrificed and the percentage of nodule incidence and all biochemical parameters, including liver cancer markers were analyzed along with histopathological investigation in the experimental animals. The rats treated with butanol fraction of ethanol extract of Gardenia gummifera L.f root bark (BUGG) remarkably repressed the NDEA-induced increase of hepatic nodule incidence, nodule multiplicity, serum biochemical indices. They improved the normal hepatocellular architecture in the toxic group. Also, the biochemical analysis of treated groups revealed that BUGG neutralizes NDEA-induced oxidative stress by restoring antioxidant enzymes. In NDEA administered rats the decreased concentration of proliferative marker, alpha fetoprotein (AFP) was observed upon the supplementation of BUGG. Notably, 200 mg/kg bw BUGG supplementation showed better results than the standard drug-treated group. These results might be linked with the improvement of antioxidant activity and inhibition of hepatic cell proliferation. The conclusions of the present investigation highlight the curative effect of BUGG against the chemical carcinogenesis model and the study suggests that BUGG can be a promising source of chemopreventive, HCC inhibiting agent.